The Application of Recent E-recruitment Trends in the Real World : Qualitative Study - Hildebrandt, Anne; Háša, Stanislav, 1974-; Brunet-Thornton, Richard; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
The research study investigates how theoretical e-recruitment trends are applied in the real world by exploring the current best practices among the survey companies related to e-recruitment. Through a blend of primary and secondary research, trends were identified and assessed to recognise the applications which are successful in the companies interviewed. Speaking to human resources employees showed that companies all utilise e-recruitment but are in different levels of its technological advancement. The literature identified trends and suggested opportunities for the interviewed companies to increase their competitiveness by investing into new developments. The investigation showed that currently, algorithms, machine learning and artificial intelligence are being utilised, either in an ATS, or mainly through sourcing. Another outcome of the study is the unawareness and knowledge deficit that leads to the lack of realising the benefits these applications can contribute to.Although the majority of the interviewed companies are not heavily employing current trends, participation in this research might have helped them understand that this is where the future of e-recruitment lies. Recommendations of how the surveyed companies should cope with the quickly changing environment and continuously changing trends were formulated.
Vedoucí práce: Stanislav Háša
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses